2010
DOI: 10.4314/ijest.v2i5.60131
|View full text |Cite
|
Sign up to set email alerts
|

The impact damage response of plain woven natural silk/epoxy laminated composite plates

Abstract: This paper presents the impact response of woven natural silk (WNS)/Epoxy composite. The composite specimens were prepared in configurations of 10, 15, 20, 25 and 30 ply of WNS. Drop weight impact test was carried out under varied impact energies of 32J, 48J and 64J. Examinations of load bearing capability, energy absorption capability and damage process from initiation of damage to final perforation, with regards to increasing number of WNS Ply and increasing impact loads were investigated. It was observed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Furthermore, Azrin Hani et al [8] in her study of hybrid (woven coir/kevlar) composites explores the potential of coconut coir to resist high speed impact penetration by reducing the amount of synthetic fibre used in composites. On the other hand, as reported in Ude et al [9], woven natural silk/epoxy/foam was seen as better energy absorber where the results displayed better load bearing capability qualities. Literature in hand reveals that no single group of researchers has completely characterised the mechanical properties of woven coir and woven kenaf for 10 m/s (meter per second) impact penetration and flexural strength.…”
Section: Introductionsupporting
confidence: 60%
“…Furthermore, Azrin Hani et al [8] in her study of hybrid (woven coir/kevlar) composites explores the potential of coconut coir to resist high speed impact penetration by reducing the amount of synthetic fibre used in composites. On the other hand, as reported in Ude et al [9], woven natural silk/epoxy/foam was seen as better energy absorber where the results displayed better load bearing capability qualities. Literature in hand reveals that no single group of researchers has completely characterised the mechanical properties of woven coir and woven kenaf for 10 m/s (meter per second) impact penetration and flexural strength.…”
Section: Introductionsupporting
confidence: 60%
“…The tensile strength of PCL-woven composite is higher than those of PCL-knitted and PCL-nonwoven materials due to a large amount of straight geometry fibres present in the woven fabric [26]. Some researchers fabricated stacking of silk fabric layers for the preparation of composite using epoxy resin [2731], whereas the present study focuses on the stacking of silk fabric with biodegradable PCL.…”
Section: Introductionmentioning
confidence: 99%
“…50,51 In low velocity impact response of plain woven silk/epoxy composites, it was revealed that with the increase in number of plies load bearing capacity and energy absorption capacity of the composite was increased but delamination and area of damage were increased. 52 Woven hemp/epoxy composites showed comparable low velocity impact and cyclic fatigue response with the glass/epoxy composites. 53…”
Section: Introductionmentioning
confidence: 87%